A boron-nitrogen-rich carbon material anchored by an iron single atom with controllable coordination environment and its application

The single-atom iron-anchored boron-rich nitrogen-carbon material with controllable coordination environment is prepared through a one-step calcination method, which solves the problems of low catalytic activity and poor stability of existing electrocatalytic ammonia synthesis and lithium-sulfur battery electrode materials, and achieves efficient electrocatalysis Synthetic ammonia and lithium-sulfur battery performance improvements.

CN115852393BActive Publication Date: 2025-01-17UNIV OF JINAN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211278628.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2025-01-17
Estimated Expiration
2042-10-19

AI Technical Summary

Technical Problem

The existing electrocatalytic synthesis of ammonia and lithium-sulfur battery electrode materials have problems such as low catalytic activity, poor stability and high cost, especially the coordination environment regulation of single-atom catalytic materials in the field of electrocatalytic nitrogen reduction is difficult to achieve.

Method used

A single-atom iron-anchored boron-rich nitrogen-carbon material with controllable coordination environment was prepared through a one-step calcination method. Iron salt, urea, boric acid and soluble starch were used as raw materials to control the nitrogen-boron coordination environment of the iron single atom for electrocatalysis. Nitrogen reduction to synthesize ammonia and lithium-sulfur batteries.

Benefits of technology

It realizes the regulation of the coordination environment of iron single atoms, significantly improves the catalytic activity and stability of electrocatalytic ammonia synthesis, and improves the area capacity and durability of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115852393B_ABST
    Figure CN115852393B_ABST
Patent Text Reader

Abstract

The invention discloses a boron-rich nitrogen-carbon material anchored by a single iron atom with a controllable coordination environment and its application. The boron-rich nitrogen-carbon material anchored by a single iron atom with a controllable coordination environment is prepared by sequentially adding iron salt, urea, boric acid, and soluble starch into water, and rapidly stirring at low temperature to form a gel precursor; the gel precursor is obtained by calcining under an inert atmosphere. The single iron atom catalytic material prepared by the present invention can achieve the regulation of the nitrogen-boron coordination environment of the single iron atom by a one-step calcination method, and the boron and nitrogen contents in the material are both 5 to 20wt%, and the coordination environment of the single Fe atom is at least one of Fe-N3B1, Fe-N2B2, or Fe-N1B3. The material is used in electrocatalytic nitrogen reduction to synthesize ammonia and lithium-sulfur batteries with remarkable effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic electrode materials and lithium-sulfur battery electrode materials, and in particular to an iron single atom anchored boron-nitrogen-rich carbon material with a controllable coordination environment and applications thereof. Background Art

[0002] Developing new sustainable energy technologies is an important task in modern chemistry, which requires the development of advanced electrocatalytic or battery electrode materials. Transition metals have been widely used as primary electrode materials for important electrochemical reactions and electrode half-reactions. Currently, the most commonly used high-efficiency electrode materials are based on precious metal nanoparticles. However, despite their obvious activity, their high cost, low natural abundance and stability have seriously hindered the commercialization process. An intuitive strategy to alleviate such problems is to reduce the size of nanoparticles, thereby reducing the cost of electrode materials. Single metal atoms embedded in specific supports show great potential in the development of energy conversion and storage materials due to the maximum utilization and mass activity of atoms. When single metal atoms are stabilized by coordination bonds with the substrate, strong metal-support interactions can be used to directly manipulate the catalytic activity of the site and the selectivity for the target reaction.

[0003] In the field of energy conversion, compared with the Haber-Bosch process with huge energy consumption and harsh conditions, electrochemical nitrogen reduction ammonia synthesis has many advantages, such as mild reaction conditions, high cost-effectiveness and sustainable production driven by renewable energy. Based on the essence of synthetic ammonia: ammonia synthesis can be achieved as long as there is a suitable proton source and electron donor. However, the current electrochemical synthesis of ammonia still has many shortcomings, such as low ammonia yield, low Faraday efficiency, poor stability of catalytic materials, etc. It strongly relies on electrocatalytic materials with low reaction barriers and high catalytic activity. Although single-atom catalytic materials have been reported for a long time, there is still little research on their work in the field of electrocatalytic nitrogen reduction by regulating the coordination environment. For example, the patent with application number 201910583136.2 discloses boron-carbon-nitrogen electrocatalytic materials and their preparation methods and applications in nitrogen reduction ammonia synthesis, but the boron and nitrogen content of the material is low and the coordination environment is uncontrollable.

[0004] In the field of energy storage, lithium-sulfur batteries have the characteristics of high energy density and low cost, but there are problems with soluble lithium polysulfide shuttling and sluggish redox kinetics. The rational design of carbon-supported single-atom catalysts as soluble lithium polysulfide immobilizers and sulfur redox promoters is of great significance for high-load, electrolyte-poor lithium-sulfur batteries. However, the most popular non-polar porphyrin-like transition metal nitrogen single-atom catalysts cannot maximize the catalytic activity of the metal center. The nitrogen atoms near the metal active center have a large electronegativity, but this can easily lead to a high reaction energy barrier for LiPS conversion, thereby weakening the sulfur redox kinetics. For example, the patent with application number 202010024502.3 discloses boron / nitrogen dual-doped porous carbon nanosheets and their lithium-sulfur battery positive electrode materials, which do not contain metal single atoms, and boron and nitrogen appear in the form of doping with low doping amounts.

[0005] In summary, solving the atomic configuration of the metal coordination part is a key step in establishing a clear relationship between single-atom structure and activity. Therefore, it is necessary to design and prepare a single-atom material with a controllable coordination environment so that it can be used for electrocatalytic synthesis of ammonia and lithium-sulfur batteries. Summary of the invention

[0006] In view of the above-mentioned prior art, the purpose of the present invention is to provide a boron-rich nitrogen-carbon material anchored by an iron single atom with a controllable coordination environment and its application. The iron single atom catalytic material prepared by the present invention can achieve the regulation of the nitrogen-boron coordination environment of the iron single atom by a one-step calcination method, and has significant effects in electrocatalytic nitrogen reduction synthesis of ammonia and lithium-sulfur batteries.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a method for preparing a boron-nitrogen-rich carbon material anchored by an iron single atom with a controllable coordination environment, comprising the following steps:

[0009] (1) adding iron salt, urea, boric acid, and soluble starch into water in sequence, and rapidly stirring at low temperature to form a gel precursor;

[0010] (2) The gel precursor is calcined under an inert atmosphere to obtain an iron single atom-anchored boron-nitrogen-rich carbon material with a controllable coordination environment.

[0011] Preferably, in step (1), the low temperature is from room temperature to 60°C.

[0012] Preferably, in step (1), the iron salt is ferrous acetate, ferrous chloride, or ferrous nitrate.

[0013] Preferably, in step (1), the molar ratio of the boric acid to the iron salt is 100-500:1, the mass ratio of the boric acid to the soluble starch is 1:1-20, and the molar ratio of the boric acid to the urea is 0.1-2:1.

[0014] Preferably, in step (2), the calcination is as follows: the starting temperature is room temperature, the temperature is raised to 1000-1500° C., and the temperature is kept for 1-6 hours; the heating rate of the calcination is 1-10° C. / min.

[0015] The second aspect of the present invention provides an iron single atom anchored boron-nitrogen-rich carbon material with controllable coordination environment prepared by the above preparation method.

[0016] Preferably, the content of boron and nitrogen in the iron single atom anchored boron-nitrogen-rich carbon material with controllable coordination environment is 5-20wt% and the content of the iron single atom is 0.5-3wt%.

[0017] Preferably, the coordination environment of the iron single atom with controllable coordination environment anchoring the Fe single atom in the boron nitrogen-rich carbon material is at least one of Fe-N3B1, Fe-N2B2 or Fe-N1B3.

[0018] Preferably, the molar ratio of the raw materials boric acid and urea is 0.1:1, and the coordination environment of the iron single atom with controllable coordination environment anchoring the Fe single atom in the boron-rich nitrogen-carbon material is Fe-N3B1; the molar ratio of the raw materials boric acid and urea is 0.5:1, and the coordination environment of the iron single atom with controllable coordination environment anchoring the Fe single atom in the boron-rich nitrogen-carbon material is Fe-N2B2; the molar ratio of the raw materials boric acid and urea is 2:1, and the coordination environment of the iron single atom with controllable coordination environment anchoring the Fe single atom in the boron-rich nitrogen-carbon material is Fe-N1B3.

[0019] The third aspect of the present invention provides the use of an iron single atom anchored boron-nitrogen-rich carbon material with a controllable coordination environment in catalyzing nitrogen reduction to synthesize ammonia or prepare a lithium-sulfur battery.

[0020] A fourth aspect of the present invention provides a lithium-sulfur battery electrode, which is prepared by the following method:

[0021] (1) mixing and grinding a single-atom-anchored boron-nitrogen-carbon material with a controllable coordination environment and sublimated sulfur, and heating in a sealed environment to obtain a single-atom-anchored boron-nitrogen-carbon electrocatalytic material containing sulfur;

[0022] (2) The sulfur-containing iron single atom anchored boron nitrogen-rich carbon electrocatalytic material, conductive carbon, and polyvinylidene fluoride binder are dispersed in an N-methyl-2-pyrrolidone solvent, and the mixture is evenly mixed by ball milling to obtain a slurry; the slurry is then cast onto an aluminum current collector and vacuum dried to obtain a lithium-sulfur battery electrode.

[0023] Preferably, the mass ratio of the iron single atom anchored boron nitrogen carbon material with controllable coordination environment to the sublimated sulfur is 3:7; the heating temperature is 155°C and the time is 12 hours; the mass ratio of the sulfur-containing iron single atom anchored boron nitrogen carbon electrocatalytic material to the conductive carbon and polyvinylidene fluoride adhesive is 8:1:1.

[0024] Beneficial effects of the present invention:

[0025] 1. The present invention adopts a simple one-step calcination, and realizes the coordination environment regulation of iron single atoms by optimizing the precursor sample and process, and the preparation process is simple and controllable. While realizing the coordination environment regulation, the substrate for anchoring single atoms is improved, breaking through the traditional pure carbon material, and preparing a boron-nitrogen-rich carbon material with better physical and chemical properties. The entire preparation reaction system is simple, easy to operate, easy to control, and highly repeatable.

[0026] 2. The porous structure of the iron single atom anchored boron-nitrogen-carbon electrocatalytic material with controllable coordination environment prepared by the present invention effectively realizes the optimization of the gas-liquid-solid three-phase reaction interface. At the same time, more exposure of single-atom catalytic sites and optimization of the electronic environment on the substrate further enhance the catalytic activity of electrocatalytic ammonia synthesis.

[0027] 3. The iron single atom anchored boron nitrogen carbon electrocatalytic material with controllable coordination environment prepared by the present invention can quickly capture soluble lithium polysulfides through strong Lewis acid-base interactions, reduce the barrier of lithium-sulfur deposition and decomposition, enhance the bidirectional sulfur oxidation catalytic reaction, and then enhance the area capacity and durability of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Transmission electron microscopy of the iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the present invention.

[0029] Figure 2 A spherical aberration-corrected transmission electron microscope for preparing a single-atom iron-anchored boron-nitrogen-rich carbon electrocatalytic material with a controllable coordination environment according to the present invention.

[0030] Figure 3 The Mössbauer spectrum of the iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the present invention.

[0031] Figure 4 Scanning electron microscope elemental analysis of the iron single atom anchored boron-nitrogen-carbon electrocatalytic material with controllable coordination environment prepared by the present invention, a is a scanning electron microscope image, b is an iron element distribution map, c is a boron element distribution map, d is a nitrogen element distribution map, e is a carbon element distribution map, and f is an elemental analysis spectrum.

[0032] Figure 5 Synchrotron radiation spectrum of the iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the present invention.

[0033] Figure 6 The graph is a current-time curve of synthesizing ammonia using the iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the present invention.

[0034] Figure 7 This is a diagram showing the catalytic performance of synthesizing ammonia using the iron single atom anchored boron nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the present invention.

[0035] Figure 8 This is a rate performance diagram of a lithium-sulfur battery using the iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the present invention.

[0036] Fig. 9 This is a multi-cycle stability diagram of a lithium-sulfur battery using the iron single atom anchored boron-nitrogen-carbon electrocatalyst material with controllable coordination environment prepared by the present invention.

[0037] Fig.10 The initial charge-discharge curve and cycle performance diagram of a soft-pack battery are constructed for a lithium-sulfur battery using the iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the present invention.

[0038] Fig.11 This is the transmission electron microscope of Comparative Example 3 of the present invention.

[0039] Fig.12 This is the spherical aberration corrected transmission electron microscope of comparative example 3 of the present invention. DETAILED DESCRIPTION

[0040] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0041] As introduced in the background technology section, the current boron-carbon-nitrogen materials are mainly doped with boron and nitrogen, and the boron-nitrogen doping amount is relatively low, generally around 0.5-3wt%. In order to improve the performance of the material, in addition to increasing the doping amount of boron and nitrogen, metal single atoms can also be doped. However, the nitrogen atoms near the metal active center have a large electronegativity, which can easily lead to a high reaction energy barrier for LiPS conversion, thereby weakening the sulfur redox kinetics.

[0042] Based on this, the purpose of the present invention is to provide a boron-nitrogen-rich carbon material anchored by a single iron atom with a controllable coordination environment and its application. What is prepared by the present invention is not a boron-nitrogen doped carbon material, because the content of boron and nitrogen is significantly increased; it no longer appears in the form of doping, but forms a boron-nitrogen-rich carbon material. Through research, it is found that only by using soluble starch as a carbon source can a boron-nitrogen-rich carbon material anchored by a single iron atom with a controllable coordination environment be obtained. By adjusting the dosage relationship of boric acid and urea, a boron-nitrogen-rich carbon material in which the coordination environment of the Fe single atom is Fe-N3B1, Fe-N2B2 or Fe-N1B3 is obtained.

[0043] While adjusting the single-atom coordination, the surface electronic structure and physicochemical properties of the substrate boron-nitrogen-carbon material that anchors the single atom are also adjusted. When adding soluble starch, the amount of urea is adjusted, and a large number of porous structures are constructed in the process of preparing the material, which is conducive to the adsorption of sulfur in lithium-sulfur batteries. At the same time, by introducing nitrogen to optimize the surface electronic structure, the electronic transport performance of carbon materials is improved, and the excellent conductivity lays the foundation for its application in electrocatalysis and lithium-sulfur batteries. After the introduction of boron, boron, as a Lewis acid site, can provide a good adsorption site for nitrogen molecules with lone pairs of electrons, which can synergize with iron single atoms to optimize the migration path of nitrogen reduction reaction intermediates, thereby improving the catalytic performance.

[0044] Iron single atoms can act as soluble lithium polysulfide immobilizers and sulfur redox promoters, which is of great significance for promoting the development of high-load, electrolyte-poor lithium-sulfur batteries. Conventional nonpolar porphyrin-like nitrogen-coordinated transition metal single atoms (M-N4) cannot maximize the catalytic activity of the metal center. Asymmetric N x -Fe-B y The configuration not only rapidly captures soluble lithium polysulfides via strong Lewis acid-base interactions but also greatly catalyzes the bidirectional sulfur redox chemistry by lowering the lithium sulfide deposition / decomposition energy barrier, thereby effectively solving the problem of soluble lithium polysulfide shuttling and sluggish redox kinetics.

[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0046] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0047] Embodiment 1:

[0048] 174 mg of ferrous acetate (0.1 mmol), 6 g of urea (100 mmol), 2 g of boric acid (30 mmol), and 5 g of soluble starch were added to water in sequence, and stirred rapidly at low temperature at 60°C and normal pressure to obtain a gel precursor; the gel precursor was placed in a programmed temperature tube furnace, and in an inert argon atmosphere, a boron-nitrogen-rich carbon material anchoring a single iron atom was obtained by programmed temperature calcination. The programmed temperature increase rate was 5°C / min, the starting temperature was room temperature, the temperature was maintained at 1100°C, and the insulation time was 2 hours.

[0049] pass Figure 1 and Figure 2 Transmission electron microscopy and spherical aberration corrected transmission electron microscopy observations show that the sample structure is a hollow porous structure, and there are obvious single atoms inside the material. Figure 3 The Mössbauer spectrum shows obvious symmetrical peaks, indicating that the iron atom exists in a single atomic state. Figure 4 Scanning electron microscopy elemental analysis showed that the content of single-atom iron was 1.6wt%, and the contents of boron and nitrogen were 8.2wt% and 7.3wt%, respectively. Figure 5 Synchrotron radiation further proved that the coordination environment of single iron atoms is mainly Fe-N2B2.

[0050] The iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment prepared by the above method is applied to electrocatalytic nitrogen reduction to synthesize ammonia. The specific steps are: in a nitrogen-saturated 0.1 mol / L sodium sulfate solution, a three-electrode reaction device is used, with precious metal platinum as the counter electrode, Ag / AgCl as the reference electrode, and the material electrode as the working electrode. Under the assistance of an electric field, the change of the electrocatalytic nitrogen fixation to synthesize ammonia with voltage is tested, such as Figure 6 and 7 As shown; Figure 6 The current-time curve of synthetic ammonia at different voltages maintains good electrochemical stability. Figure 7 The performance comparison of nitrogen fixation under different potentials is shown in the figure. It can be seen from the figure that the optimal voltage is -0.2V, and the yield of synthetic ammonia is 115μg h -1 mg -1 , and the Faraday efficiency is 24%. In summary, the iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material with controllable coordination environment has good electrocatalytic nitrogen reduction performance for ammonia synthesis.

[0051] The iron single atom anchored boron-nitrogen-carbon electrocatalyst material with controllable coordination environment prepared by the above method is applied to lithium-sulfur batteries, and the specific steps are: the prepared iron single atom anchored boron-nitrogen-carbon electrocatalyst material and sublimated sulfur are continuously ground in a mass ratio of 3:7, and heated in a sealed vial at 155°C for 12 hours. Subsequently, the iron single atom anchored boron-nitrogen-carbon electrocatalyst material containing sulfur is dispersed in N-methyl-2-pyrrolidone solvent with conductive carbon and polyvinylidene fluoride binder, and the mass ratio of the three feeds is 8:1:1, and the slurry is evenly mixed by ball milling to obtain a slurry. The slurry is then cast onto an aluminum current collector and vacuum dried to obtain a lithium-sulfur battery electrode. The lithium-sulfur battery based on the iron single atom anchored boron-nitrogen-carbon electrocatalyst material with controllable coordination environment has an ultra-long life. After 1000 cycles at 5C, its capacity remains at nearly 82% of the initial capacity. The sulfur loading is 12.0 mg S cm -2 , E / S ratio is 5 μL mg S -1 , at 2.0 mA cm -2 After 100 cycles, it can maintain 9.2 mAh cm -2 The surface capacity ( Figure 8 ). At the same time, the construction is as high as 11.6mg· S cm -2 The sulfur loading was 3 μL mg S -1 The lean electrolyte / sulfur ratio and 1.5 positive / negative electrode capacity ratio were used to successfully build a 0.3Ah soft-pack battery with a capacity of 359Wh kg -1 Energy density output ( Fig. 9 ).

[0052] Example 2

[0053] The preparation method is the same as that of Example 1, except that the iron salt is ferrous chloride.

[0054] Example 3

[0055] The preparation method is the same as that of Example 1, except that the iron salt is ferrous nitrate.

[0056] Example 4

[0057] The preparation method is the same as that of Example 1, except that the molar ratio of boric acid to iron salt is 100: 1. That is, the raw materials required to be added during the synthesis process are 522 mg ferrous acetate (0.3 mmol), 6 g urea (100 mmol), 2 g boric acid (30 mmol), and 5 g soluble starch.

[0058] Example 5

[0059] The preparation method is the same as that of Example 1, except that the molar ratio of boric acid to iron salt is 500: 1. That is, the raw materials required to be added during the synthesis process are 104 mg ferrous acetate (0.06 mmol), 6 g urea (100 mmol), 2 g boric acid (30 mmol), and 5 g soluble starch.

[0060] Example 6

[0061] The preparation method is the same as that in Example 1, except that the mass ratio of boric acid to soluble starch is 1: 1. That is, the amount of raw materials added during the synthesis process is 174 mg ferrous acetate (0.1 mmol), 6 g urea (100 mmol), 2 g boric acid (30 mmol), and 2 g soluble starch.

[0062] Example 7

[0063] The preparation method is the same as that in Example 1, except that the mass ratio of boric acid to soluble starch is 1:20. That is, the amount of raw materials added during the synthesis process is 174 mg of ferrous acetate (0.1 mmol), 6 g of urea (100 mmol), 2 g of boric acid (30 mmol), and 40 g of soluble starch.

[0064] Example 8

[0065] The preparation method is the same as that of Example 1, except that the molar ratio of boric acid to urea is 0.1:1. That is, the amount of raw materials required to be added during the synthesis process is 174 mg of ferrous acetate (0.1 mmol), 18 g of urea (300 mmol), 2 g of boric acid (30 mmol), and 5 g of soluble starch. Figure 5 As shown, the synchrotron radiation spectrum of the iron single atom anchored in the boron-nitrogen-carbon material with controllable coordination environment shows that the coordination environment of the Fe single atom is mainly Fe-N3B1.

[0066] Example 9

[0067] The preparation method is the same as that of Example 1, except that the molar ratio of boric acid to urea is 2:1. That is, the amount of raw materials required to be added during the synthesis process is 174 mg of ferrous acetate (0.1 mmol), 0.9 g of urea (15 mmol), 2 g of boric acid (30 mmol), and 5 g of soluble starch. Figure 5 As shown, the synchrotron radiation spectrum of the iron single atom anchored in the boron-nitrogen-carbon material with controllable coordination environment shows that the coordination environment of the Fe single atom is mainly Fe-N1B3.

[0068] Example 10

[0069] The preparation method is the same as that in Example 1, except that the programmed heating rate is 1°C / min.

[0070] Embodiment 11

[0071] The preparation method is the same as that in Example 1, except that the programmed heating rate is 10°C / min.

[0072] Example 12

[0073] The preparation method is the same as that of Example 1, except that the temperature is maintained at 1000°C.

[0074] Embodiment 13

[0075] The preparation method is the same as that of Example 1, except that the temperature is maintained at 1500°C.

[0076] Embodiment 14

[0077] The preparation method is the same as that of Example 1, except that the high temperature calcination is maintained for 1 hour.

[0078] Embodiment 15

[0079] The preparation method is the same as that of Example 1, except that the high temperature calcination is maintained for 6 hours.

[0080] Comparative Example 1

[0081] (1) Precursor synthesis

[0082] 6 g urea (10 mmol), 0.15 g boric acid (2.5 mmol) and 1.5 g polyethylene glycol 4000 were dissolved in deionized water until completely dissolved, added to a 5 cm×5 cm carbon paper substrate, and then evaporated to dryness at 80° C. and normal pressure.

[0083] (2) Calcination to prepare the final product

[0084] The carbon paper with a mixture of urea, boric acid and polyethylene glycol 4000 evenly distributed was placed in a corundum porcelain boat, which was then placed in a programmed temperature tube furnace and calcined in an argon atmosphere to obtain a boron-carbon-nitrogen electrocatalytic ammonia synthesis material. In an argon atmosphere, the heating rate was 5°C / min, the starting temperature was room temperature, the temperature was maintained at 950°C, the insulation time was 2 hours, and the temperature was naturally lowered after the reaction to obtain a boron-carbon-nitrogen electrocatalytic material.

[0085] The yield of ammonia synthesis by the boron-carbon-nitrogen electrocatalyst is 8.2 μg·h -1 cm -2 . The Faradaic efficiency is 7% at -0.3V.

[0086] Comparative Example 2

[0087] Step 1, preparation of boron / nitrogen dual-doped porous carbon nanosheets:

[0088] Weigh 80mmol (4.8g) of urea, 2.5mmol (0.1545g) of boric acid and 0.25mmol (0.5g) of polyethylene glycol-2000, add them into 50mL of deionized water and stir evenly, evaporate the resulting solution to dryness to obtain a white powder; put the resulting white powder precursor into a tubular furnace, heat it to 900°C at a rate of 5°C / min under an argon atmosphere, carbonize it for 2h, and finally cool it to room temperature to obtain a boron / nitrogen dual-doped porous carbon nanosheet;

[0089] Step 2, compounding the boron / nitrogen dual-doped porous carbon nanosheets obtained in step 1 with sulfur:

[0090] Boron / nitrogen dual-doped porous carbon nanosheets and sulfur element are mixed in a mass ratio of 1:4, ground to obtain a mixture of boron / nitrogen dual-doped porous carbon nanosheets and sulfur, and placed in a crucible for later use; the crucible containing the mixture is placed in a polytetrafluoroethylene reactor under an argon atmosphere and sealed; the sealed reactor is transferred to an oven at 155°C and kept warm for 12 hours; and cooled to room temperature to obtain a lithium-sulfur battery positive electrode material (S / BN-CN Ss-1).

[0091] The sulfur loading content of the material was 76.1% after 100 cycles at 0.5C. Its capacity retention and sulfur loading capacity were lower than those of the material prepared by the present invention.

[0092] Comparative Example 3

[0093] The difference from Example 1 is that the soluble starch is replaced with polyethylene glycol-2000. Single-atom iron cannot be prepared. Spherical aberration transmission electron microscopy shows that a large number of carbide particles agglomerate in the boron-nitrogen-carbon material substrate (such as Figure 11-12 shown).

[0094] The present invention obtains a boron-nitrogen-rich carbon electrocatalytic material anchored by a single iron atom with a controllable coordination environment by a simple calcination method. The hollow porous structure is characterized by transmission electron microscopy and a boron-nitrogen-rich carbon electrocatalytic material anchored by a single iron atom with a controllable coordination environment, and there are uniformly distributed single iron atoms inside. The various coordination environments of single iron atoms are confirmed by Mössbauer spectroscopy and synchrotron radiation. The prepared material is used as a working electrode, which exhibits excellent electrocatalytic ammonia synthesis activity, and the material electrode maintains high stability. At the same time, it is used for lithium-sulfur batteries and exhibits excellent high area capacity and ultra-high sulfur loading. Therefore, the material of the present invention has important application value in the fields of electrocatalytic ammonia synthesis and lithium-sulfur batteries.

[0095] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A single-atom iron-anchored boron-nitrogen-carbon material with controllable coordination environment, characterized in that: The boron and nitrogen contents in the iron single atom anchored boron-nitrogen-carbon material with controllable coordination environment are both 5-20wt%; the content of the iron single atom is 0.5-3wt%; the coordination environment of the Fe single atom in the iron single atom anchored boron-nitrogen-carbon material with controllable coordination environment is at least one of Fe-N3B1, Fe-N2B2 or Fe-N1B3; The iron single atom anchored boron-nitrogen-rich carbon material with controllable coordination environment is prepared by the following method: (1) adding iron salt, urea, boric acid and soluble starch into water in sequence, and stirring rapidly at low temperature to form a gel precursor; the molar ratio of the boric acid to the iron salt is 100 to 500:1, the mass ratio of the boric acid to the soluble starch is 1:1 to 20, and the molar ratio of the boric acid to the urea is 0.1 to 2:1; (2) The gel precursor is calcined in an inert atmosphere to obtain an iron single atom anchored boron nitrogen-rich carbon material with a controllable coordination environment; the calcination is as follows: the starting temperature is room temperature, the temperature is increased to 1000-1500°C, and the temperature is kept for 1-6 hours; the calcination heating rate is 1-10°C / min.

2. The iron single atom anchored boron-nitrogen-carbon material with controllable coordination environment according to claim 1, characterized in that: In step (1), the iron salt is ferrous acetate, ferrous chloride or ferrous nitrate.

3. Use of the iron single atom anchored boron-nitrogen-rich carbon material with controllable coordination environment as described in claim 1 or 2 in catalyzing nitrogen reduction to synthesize ammonia or preparing lithium-sulfur batteries.

4. A lithium-sulfur battery electrode, characterized in that: Prepared by the following method: (1) The iron single atom anchored boron-nitrogen-rich carbon material with controllable coordination environment as claimed in claim 1 or 2 is mixed with sublimated sulfur and ground, and heated in a sealed environment to obtain an iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material containing sulfur; (2) The sulfur-containing iron single atom anchored boron-nitrogen-rich carbon electrocatalytic material, conductive carbon, and polyvinylidene fluoride binder are dispersed in N-methyl-2-pyrrolidone solvent and mixed evenly by ball milling to obtain a slurry; the slurry is then cast onto an aluminum current collector and vacuum dried to obtain a lithium-sulfur battery electrode.

5. The lithium-sulfur battery electrode according to claim 4, characterized in that: The mass ratio of the iron single atom anchored boron nitrogen carbon material with controllable coordination environment to the sublimated sulfur is 3:7; the heating temperature is 155°C and the time is 12 hours; the mass ratio of the sulfur-containing iron single atom anchored boron nitrogen carbon electrocatalytic material to the conductive carbon and polyvinylidene fluoride adhesive is 8:1:1.

Citation Information

Patent Citations

  • Boron, carbon, and nitrogen electrocatalytic materials, their preparation methods, and their application in nitrogen reduction for ammonia synthesis.

    CN110193374B

  • Boron / nitrogen double-doped porous carbon nanosheet and lithium-sulfur battery positive electrode material thereof

    CN111170306A

  • Preparation method of catalyst for nitrogen reduction reaction

    CN114700100A